VALIDITAS DAN RELIABILITAS ANGKET KEMANDIRIAN BELAJAR - Nazmi Nabila Putri; Nandang Rukanda; Wiwin Yuliani (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
Learning independence plays an significant role in edification, in addition to step in as a student's ability to voluntarily carry out learning activities without depending on others. This is done patiently and leads to the achievement of the desired goals of students and also plays a role in making decisions about student learning outcomes and achievements. Therefore, a learning independence measurement tool is needed in the form of a learning independence questionnaire, while it has passed the validity test stage and the credibility test stage. The data collection for this analysis is 30 students of SMAN 1 CIANJUR grade XI. The stage that passed the validity test of the 20 expressions contained 10 questions which were shown to be correct and the validity test received a value of 0.718 while it was meaningfully classified as the outer part. Thus, the list of 71% learning independence inquiry can be apply to measure the level of student self-studyKeywords:Independent Learning, Validity, Reliability